1987
DOI: 10.1111/j.1365-3083.1987.tb02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Rat C3 Conversion by Rat Anti‐2,4, Dinitrophenyl (DNP) Hapten IgA Immune Precipitates

Abstract: Monomeric (m-) and polymeric (p-) anti-DNP monoclonal (MC) rat IgA antibodies (Ab) were tested for precipitation with DNP-bovine serum albumin (DNP-BSA) and C3 conversion in rat serum, with rat MC anti-DNP IgG2b used as reference. At equivalence, p-IgA rapidly precipitated DNP-BSA, with little antigen (Ag) left in the supernatant. In contrast, m-IgA at five-fold higher concentration precipitated Ag very slowly, with less than 50% of Ag precipitated at equivalence. The Ag/Ab weight ratio at equivalence was 0.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1988
1988
1993
1993

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This reaction occurs via the alternative pathway (AP) [46] .Very recently, Schneiderman et al [47] described 2 different rabbit-mouse chimeric transfectomas of the IgA isotype directed against dansyl hapten. Those IgA antibodies also activate C via the AP Which pathway of C activation was involved in our present in vivo studies is a matter of further investigation, but in vitro studies have shown involvement of the AP [24,25]. Although immune precipitates of aIgA induced some C4 consumption in vitro [25], recent in vivo studies with d g A , dIgA and pIgA could not demonstrate deposition of C4 on IgA in vivo (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 68%
“…This reaction occurs via the alternative pathway (AP) [46] .Very recently, Schneiderman et al [47] described 2 different rabbit-mouse chimeric transfectomas of the IgA isotype directed against dansyl hapten. Those IgA antibodies also activate C via the AP Which pathway of C activation was involved in our present in vivo studies is a matter of further investigation, but in vitro studies have shown involvement of the AP [24,25]. Although immune precipitates of aIgA induced some C4 consumption in vitro [25], recent in vivo studies with d g A , dIgA and pIgA could not demonstrate deposition of C4 on IgA in vivo (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 68%
“…Rat C3, C4 and C5 were titrated by specific hemolytic assays using EA (SRBC coated with a subagglutinating amount of rabbit IgG anti-sheep RBC) and C3DHS, C4DGPS and CSDHS, respectively [18,19,331.…”
Section: Complement Titrations 3 Resultsmentioning
confidence: 99%
“…We have reported previously that IgA IC prepared with DNPs RSA and MC rat IgA anti-DNP are able to elicit rat C3 conversion [19] and are solubilized by rat C via the AP [20]. The present studies were designed to investigate the capacities of rat MC m-, d-and p-IgA to activate the C system.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations